Heat Shock Protein 60 in Cardiovascular Physiology and Diseases - Duan, Yaoyun; Tang, Huayuan; Mitchell-silbaugh, Kali; Fang, Xi; Han, Zhen; Ouyang, Kunfu (Frontiers in Molecular Biosciences, 2020)
Heat shock protein 60 (HSP60) is a highly conserved protein abundantly expressed in both prokaryotic and eukaryotic cells. In mammals, HSP60 has been primarily considered to reside in the mitochondria, where HSP60 and HSP10 form a complex and facilitate mitochondrial protein folding. However, HSP60 is also observed in the cytoplasm, the plasma membrane, and the extracellular space. HSP60 regulates a broad spectrum of cellular events including protein trafficking, peptide hormone signaling, cell survival, cell proliferation, inflammation, and immunization. In the cardiovascular system, growing evidence indicates that HSP60 could not only play an important role under physiological conditions, but also regulate the initiation and progression of heart failure and atherosclerosis. In this review, we describe recent advances in understanding the function of HSP60 in cardiomyocytes, endothelial cells, and vascular smooth muscle cells, respectively, and discuss the related signaling pathways that have been found in these cells, so as to illustrate the role of HSP60 in the development of cardiovascular disease.